Interleukin 34 expression is associated with synovitis severity in rheumatoid arthritis patients. Issue 1 (28th October 2011) - Chemel, M; Le Goff, B; Brion, R; Cozic, C; Berreur, M; Amiaud, J; Bougras, G; Touchais, S; Blanchard, F; Heymann, M F; Berthelot, J M; Verrecchia, F; et al.
Abstract : Objectives: Interleukin (IL) 34 is a new cytokine implicated in macrophage differentiation and osteoclastogenesis. This study assessed IL-34 expression in the tissue of patients with rheumatoid arthritis (RA). Methods: Immunohistochemistry was performed in synovial biopsies from patients with RA (n=20), osteoarthritis (n=3) or other inflammatory arthritis (n=4). IL-34 was detected in the synovial fluid by ELISA and its messenger RNA expression was studied by quantitative PCR in rheumatoid synovial fibroblasts after stimulation by tumour necrosis factor α (TNFα) and IL-1β. Wild-type, jnk1 −/− –jnk2 −/− and nemo −/− murine fibroblasts and pharmacological inhibition were used to determine the involvement of nuclear factor kappa B (NF-κB) and JNK in that effect. Results: IL-34 was expressed in 24/27 biopsies, with three samples from RA patients being negative. A significant association was found between IL-34 expression and synovitis severity. Levels of IL-34 and the total leucocyte count in synovial fluid were correlated. TNFα and IL-1β stimulated IL-34 expression by synovial fibroblasts in a dose/time-dependent manner through the NF-κB and JNK pathway. Conclusion: This work for the first time identifies IL-34 expression in the synovial tissue of patients with arthritis. This cytokine, as a downstream effector of TNFα and IL-1β, may contribute to inflammation and bone erosions in RA.